PENERAPAN MODEL PEMBELAJARAN PENCAPAIAN KONSEP UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR SISWA (Penelitian Tindakan Kelas Pada Mata Pelajaran Matematika Siswa SMAN 1 Pajar Bulan Kelas XI IPA) - Al Azhar (UNIB Press, 2021)
The purpose of this study is: (1) to describe the application of the concept attainment learning model to increase students' activation in math subjects. (2) to describe the application of the concept attainment learning model to improve students' learning achievement on math subjects.(3) to describe the effectiveness of the application of the concept attainment learning model to increase activation and students' learning performance in math subjects. The method used in this study is a quantitative descriptive type of research is classroom action research (classroom action research) quasi expo. The subject of this research is the XI high school student of 1 Pajar Bulan high school. The data-collecting technique is a essay test that corresponds with An indicator of activity ability and learning achievement on the subject Trigonometry on the sinus and cosine subject. The given test it’s a ten-to-one descriptions. Research shows that the concept attainment learning model can increase activation and students’ math performance. The average activation and the performance of student mathematics taught with a learning model achieving c higher concepts than average activation and students learning achievement are taught with conventional models